ANALISIS PROFIL PENULISAN CATATAN PERKEMBANGAN PASIEN TERINTEGRASI (CPPT) APOTEKER DI RUMAH SAKIT X KOTA PEKANBARU - Novtafia Endri; Nursyafni; Ayu Rahmawati; Zhafirah Fajri F.A (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Farmasi Riau, 2026)
Healthcare services in hospitals involve various health professionals, including pharmacists, who play a vital role in pharmaceutical care and interprofessional communication. The documentation of the Integrated Patient Progress Notes (CPPT) using the SOAP method (Subjective, Objective, Assessment, Plan) is a crucial part of the pharmacist's responsibility. This study analyzes the documentation profile of pharmacists' CPPT in Hospital X, Pekanbaru. Data collection was conducted prospectively using a total sampling technique in July 2024. The results showed that out of 30 analyzed CPPTs, 100% were fully documented, but only 9 CPPTs (30%) were in accordance with the SOAP documentation standards. The subjective data was well-documented in all CPPTs, while the consistency of objective, assessment, and plan data remained low. The inconsistencies were primarily due to a lack of coherence between the data and insufficient documentation of drug-related problems. This study highlights the importance of improving pharmacists' documentation quality to support accurate clinical decision-making and enhance healthcare service quality.